A New Coverage Improvement Algorithm Based on Motility Capability of Directional Sensor Nodes - Guvensan, M. Amac; Yavuz, A. Gokhan (SPRINGER-VERLAG BERLIN, 2011)
In directional sensor networks (DSNs), motility capability of a directional sensor node has a considerable impact on the coverage enhancement after the initial deployment. Since random deployment may result in overlapped field of views (FoVs) and occluded regions, directional sensor nodes with rotatable mechanisms may reorganize their working directions to improve the coverage. Our proposed algorithm, Attraction Forces of Uncovered Points (AFUP), aims at both minimizing the overlapped areas and facing the working directions towards the area of interest. AFUP is a distributed iterative algorithm and exploits the repel forces exerted by the uncovered points around the sensor nodes. The proposed algorithm improves the coverage by 18%-25% after the initial deployment. Moreover, AFUP outperforms three well-known area coverage enhancement methods [15] [19] [16] in terms of coverage improvement and overlap minimization. Our simulation results show that AFUP converges in five iterations in most of the scenarios.
Keywords: Directional Sensor Networks; Coverage; Motility; Field of View; Repulsive Force; NETWORKS; Computer Science; Telecommunications